Hazards of lunar surface exploration: determining the immunogenicity/allergenicity of lunar dust - Colorado, Audrie A.; Gutierrez, Cody L.; Nelman-Gonzalez, Mayra; Marshall, Gailen D.; Mccoy, J. Torin; Crucian, Brian E. (Frontiers in Immunology, 2025)
Although infrequent, there have been Apollo program reports of lunar dust exposure leading to notable upper respiratory symptoms in select crewmembers. Possible mechanisms include particulate irritation, inflammation from toxic insult, or legitimate adaptive immune-mediated response. Although sterile non-protein matter would not be expected to be immunogenic, one Apollo flight surgeon reported increasing symptoms upon repeated perceived exposure with associated eosinophilia, suggestive of possible allergic reactions. Many International Space Station (ISS) crews display a pattern of persistent immune system dysregulation and latent virus reactivation. Some ISS crews manifest atypical respiratory and/or dermatitis symptoms which could have an allergic component. It is logical to anticipate crew immune dysregulation could worsen during prolonged deep space missions and planetary surface hazards will only complicate crew health risks. Allergic (i.e. mast cell-mediated) reactivity could adversely increase negative clinical and operational impacts for long-duration lunar astronauts and affect countermeasure requirements for surface vehicles. This study investigated whether lunar dust exposure could possibly elicit an IgE mediated allergic response during spaceflight by utilizing in vitro cell culture models. Our laboratory was officially approved for receipt of actual lunar dust samples from the Apollo 16 mission from NASA. These samples were used to complete the proposed set of in vitro cell culture experiments, using human peripheral blood mononuclear cells (PBMC) from healthy individuals, and basophils and eosinophil cell lines. Cells were co-cultured with cellular mitogens, common recall antigens (Der p1), fine ground silica quartz (control), or lunar dust, to study whether lunar dust exposure could alter the generation of selective immune responses associated with clinical allergic reactions. Measured outputs included supernatant-derived total IgE, tryptase, histamine, and selected cytokine levels. Cellular activation was monitored by assessing activation markers via flow cytometry. EM/x-ray analysis was used to determine cellular interactions with dust particles. The assessments in primary human blood immune cells indicated no evidence for cellular responsiveness nor ’allergy-like‘ reactivity to lunar dust. Assessments using purified ’allergic‘ cell lines, did yield some unique but mild responsiveness to lunar dust, however such cells lines can have response profiles somewhat different from their in vivo counterparts. This study determining the allergy specific immune responses, will help guide NASA to develop mitigation techniques and potential countermeasures necessary in the event of excessive exposure to lunar dust during lunar surface EVAs.